A Functional Prelithiation Separator Promises Sustainable High‐Energy Lithium‐Ion Batteries - Meng, Qinghai; Fan, Min; Chang, Xin; Li, Hongliang; Wang, Wen‐Peng; Zhu, Yu‐Hui; Wan, Jing; Zhao, Yao; Wang, Fuyi; Wen, Rui; Xin, Sen; Guo, Yu‐Guo (Advanced energy materials, 2023)
High‐energy lithium‐ion batteries built with silicon‐based anode materials are usually associated with short cycle lives due to mechanical failure at an anode level and more importantly, due to electrochemical failure at a cell level as a result of irreversible consumption of cathode Li during initial charge. (Electro)chemical prelithiation has shown promises to compensate initial Li loss and improve cycling performance of the battery. However, previous strategies applied directly at anode or cathode could raise concerns on safety and degraded electrode structure, and are less compatible with industrial manufacture of batteries. Here, a new concept of prelithiation by lithiation agents supported functional separator, which is highly adaptive to electrode preparation, battery manufacture and formation, and is capable of, by simply adjusting cell voltage, not only replenishing cathode Li loss but re‐uptaking anode Li to inhibit local over‐lithiation and dendrite formation, is shown. By employing the functional separator, a 3‐Ah Li‐ion pouch cell that pairs a silicon‐based anode and a high‐nickel layered oxide cathode demonstrates stable energy output of >330 Wh kg−1 and much improved cycling performance. A new prelithiation method based on a lithiation agents supported functional separator is proposed to compensate the Li loss during battery formation and cycling, and promises a high‐energy rechargeable lithium‐ion battery with improved safety and sustainability.